Monitoring of the development of information infrastructure in Ukraine - Prav, Roman (Technology audit and production reserves, 2018)
The object of research is the information infrastructure of Ukraine. One of the most problematic places is the lack of an assessment and monitoring system for the development of information infrastructure. It was revealed that the main drawbacks of the existing monitoring indicators are the lack of consideration of the level of information threats. Assessment of the development of information infrastructure takes place without taking into account the degree of information security of its objects. During the study, methods of system analysis were used to assess the indicators of the development of information infrastructure in the context of the level of information threats. Meta-analysis of scientific works and normative legal acts is used to systematize the scientific provisions on research issues. It is established that the system of indicators used for assessing information security is most often used, including the indicators of the level of development of information and communication technologies in the context of the main subjects of the information infrastructure. This is due to the availability of information. Due to the developed system of assessment and monitoring of the development of information infrastructure, it is possible to obtain knowledge about the level of information threats and security. Compared to similar well-known approaches to evaluation, this provides a number of benefits. In particular, it is possible to identify critical infrastructure objects that are characterized by the highest level of exposure to information threats. This approach has proved to be necessary to ensure the protection of information in the private sector of the information sphere. The assessment of the state of the information infrastructure on the basis of the developed monitoring system made it possible to identify a number of trends. The development of the information infrastructure of enterprises and technologies in the information sphere is fast-paced. This is due to the increasing level of computerization, technological re-equipment, the use of social media companies and the «big data» analysis. One of the factors is the rapid spread of cloud technologies and computing. At the same time, it enables to automate the business processes of processing and analysis of information. However, on the other hand, it serves as a source of threats to internal information and information infrastructure.